Diseño de un biodigestor de flujo inducido con el uso de corrientes térmicas (2011)
This project involves the design of an induced flow digester with the use of thermal currents to obtain biogas, its application is given to take advantage of biodegradable wastes produced by farms that are at an altitude exceeding 2,500 meters above sea level. The main advantage offered by the project is the implementation of the thermal conditioning, mechanical agitation and co-digestion, allowing for lower processing times and higher content of methane in the biogas obtained, thus achieving a higher calorific value of the biogas.